Peran Guru Dalam Membentuk Karakter Islami Pada Anak-Anak KB dan TK Ismail Global School Dengan Pendekatan Profetik - Samsudin, Ahmad (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2018)
This study aims to explore the role of teachers in shaping Islamic character in young children at KB and TK Ismail Global School through a prophetic approach. The study employs a qualitative approach with a case study method, collecting data through interviews, observations, and document analysis. The findings indicate that teachers play a strategic role in shaping Islamic character by instilling values such as honesty, compassion, and discipline through exemplary behavior and a holistic approach. Furthermore, the role of parents and the collaboration between teachers and parents are crucial in supporting the development of Islamic character. The prophetic approach applied proves to be effective in internalizing Islamic values in children, reflected in daily activities both in and outside the classroom. Keywords: Teacher Role, Islamic Character, Early Childhood, Prophetic Approach, Islamic Education, Parent Collaboration